SP10.2.1 The FLIP Study – Fluid Resuscitation in Pancreatitis. (9th August 2022) - McGovern, Julia; Tingle, Sam; ,; Moir, John; Robinson, Stuart
Abstract: Aim: Acute pancreatitis (AP) is an emergency surgical presentation which can range in severity from mild to life-threatening. Intravenous fluids are the cornerstone of management. However, there is poor quality evidence regarding optimal intravenous fluid administration. We aimed to establish clinical practice regarding intravenous fluid administration in AP and the effect this has on mortality. Methods: Prospective multi-centre audit of patients with AP. Data was collected on intravenous fluid administration within 72-hours of admission. Primary outcome was 30-day mortality and multivariable logistic regression was used to identify predictors of this. Results: 254 participants were included. Volume of intravenous fluid delivered over the first three days (median and range) are as follows; Day 1=2L (0–10.5L), Day 2=1L (0–5L), Day 3=0L (0–7.5L). Those with severe pancreatitis (Glasgow score>=3) received more fluid; median 5.7L versus 4L in 72hrs (P=0.003). The following factors were significant predictors of 30-day mortality in our multivariable model: age, Glasgow score, CRP, IHD and pancreatitis aetiology. Overall, volume of intravenous fluid was not associated with mortality in this model (adjusted OR=0.932;0.766–1.134;P=0.483). However, the effect of intravenous fluid volume on mortality differed significantly depending on pancreatitis severity (interaction term P=0.042). In the severe pancreatitis group increased volume of intravenous fluid was associated with significant reductions in mortality (OR=0.655;0.459–0.936;P=0.020). Conclusion: In severe pancreatitis more aggressive fluid prescribing is associated with decreased mortality. This is not the case in milder disease. The lack of published literature regarding the impact of fluid regime on outcomes in acute pancreatitis is reflected by the variation of fluid prescribing.